2022
DOI: 10.1200/jco.2022.40.16_suppl.4507
|View full text |Cite
|
Sign up to set email alerts
|

TRUCE-02: An open label, single-arm, phase II study of tislelizumab combined with nab-paclitaxel for high-risk non-muscle-invasive urothelial bladder carcinoma.

Abstract: 4507 Background: Pts with multiple or tumors with large invasion areas which are un-completely-resectable through TURBT would be recommended radical cystectomy in the clinical treatment. The KEYNOTE-057 study has illuminated the efficiency of immune checkpoint inhibitors monotherapy in HR-NMIBC pts, with acceptable adverse events (AEs). However, the role of PD-1/PD-L1 inhibitor in combination with chemotherapy in NMIBC pts remains unclear. We report preliminary treatment efficiency, safety data, and explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results showed that, compared with the NAC and neoadjuvant immunotherapy cohorts, patients treated with neoadjuvant T + GC achieved a significantly higher complete response rate ( p = 0.001) and pathological downstaging rate ( p = 0.007). In addition, a series of TRUCE studies were designed to evaluate the efficacy and safety of neoadjuvant tislelizumab in combination with nab‐paclitaxel in both MIBC 21 and high‐risk non‐muscle‐invasive urothelial bladder carcinoma (NMIBC) 22 . Researchers have found that the combination of tislelizumab and nab‐paclitaxel provides a novel neoadjuvant therapeutic option with a satisfactory efficacy and safety profile 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that, compared with the NAC and neoadjuvant immunotherapy cohorts, patients treated with neoadjuvant T + GC achieved a significantly higher complete response rate ( p = 0.001) and pathological downstaging rate ( p = 0.007). In addition, a series of TRUCE studies were designed to evaluate the efficacy and safety of neoadjuvant tislelizumab in combination with nab‐paclitaxel in both MIBC 21 and high‐risk non‐muscle‐invasive urothelial bladder carcinoma (NMIBC) 22 . Researchers have found that the combination of tislelizumab and nab‐paclitaxel provides a novel neoadjuvant therapeutic option with a satisfactory efficacy and safety profile 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a series of TRUCE studies were designed to evaluate the efficacy and safety of neoadjuvant tislelizumab in combination with nab‐paclitaxel in both MIBC 21 and high‐risk non‐muscle‐invasive urothelial bladder carcinoma (NMIBC). 22 Researchers have found that the combination of tislelizumab and nab‐paclitaxel provides a novel neoadjuvant therapeutic option with a satisfactory efficacy and safety profile. 21 Another retrospective study was performed to assess the efficacy of T + GC as a first‐line adjuvant treatment in patients with locally advanced or metastatic BC.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint, CR rate, was 55% at nine months. 12 The combined toxicity of two systemic drugs makes this combination unlikely to undergo further investigation in North America or Europe. Results of the CORE1 trial, however, have generated excitement in the NMIBC field.…”
Section: Bladder Cancermentioning
confidence: 99%